An interdisciplinary approach to the concept of a dematerialized business branch - Valentina Aniballi; Alessandro Avenali; Marco Marazza; Giorgio Matteucci; Fabio Nonino (Labour & Law Issues, 2023)
Based on a joint research experience between labor law and management engineering scholars, this essay aims to present to their respective scientific communities a (new) possible approach to defining the functional autonomy requirement that the transferred business unit must necessarily have to produce the effects of Article 2112 of the Civil Code. Specifically, it seeks to make available some possible qualitative and quantitative parameters for measuring the functional autonomy of a technologically dematerialized business branch that current law struggles to fully comprehend. The authors' objective is to highlight the significant assistance that any interpreter, starting from the judge, can derive from the managerial approach in the challenging process of “progressive specification and concretization” (Constitutional Court no. 110/2023) of a legal provision (Article 2112, paragraph 5, Civil Code) that undoubtedly exhibits flexibility.